2018
DOI: 10.1186/s12935-018-0574-3
|View full text |Cite
|
Sign up to set email alerts
|

Harmine, a dual-specificity tyrosine phosphorylation-regulated kinase (DYRK) inhibitor induces caspase-mediated apoptosis in neuroblastoma

Abstract: BackgroundNeuroblastoma (NB) is an early childhood malignancy that arises from the developing sympathetic nervous system. Harmine is a tricyclic β-carboline alkaloid isolated from the harmal plant that exhibits both cytostatic and cytotoxic effects. Harmine is capable of blocking the activities of dual-specificity tyrosine phosphorylation-regulated kinase (DYRK) family proteins and mitogen-activated protein kinase. These kinases promote proliferation and inhibit apoptosis.MethodsFour human NB cell lines were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
6
30
0
Order By: Relevance
“…Previous studies have reported the antitumor effects of HM on hepatocellular carcinoma (39), gastric cancer (9) and neuroblastoma (40). In the present study, the anticancer activity of HM was demonstrated using MDA-MB-231 and MCF-7 cells in vitro and MCF-7 cell-derived xenograft tumor in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the antitumor effects of HM on hepatocellular carcinoma (39), gastric cancer (9) and neuroblastoma (40). In the present study, the anticancer activity of HM was demonstrated using MDA-MB-231 and MCF-7 cells in vitro and MCF-7 cell-derived xenograft tumor in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, EGCG can potentially target many different intracellular pathways [ 177 ], making it difficult to assign particular effects to DYRK1A inhibition. Additionally, the ß-carboline alkaloid harmine selectively inhibits DYRK1A and—albeit, less efficiently—other members of the family [ 178 , 179 ], and it has been reported to have cytotoxic effects on cancer cell lines [ 66 , 85 , 180 , 181 ] and antitumor effects in vivo in glioma and in PDAC xenograft experiments [ 66 , 68 ], as well as synergistic effects with other chemotherapeutic agents [ 79 , 80 , 182 ]. However, the neurotoxic effects of harmine due to the targeting of monoamine oxidase A rule against its use in humans.…”
Section: Dyrk Inhibitors As Antitumor Therapiesmentioning
confidence: 99%
“…For example, there is a positive correlation of DYRK2 expression with patient survival in hepatocellular, non-small cell lung, pulmonary adenocarcinoma, colorectal and bladder cancers, and non-Hodgkin's lymphoma [76,77,[80][81][82][83][84]. On the contrary, other results have revealed that DYRK2 expression in neuroblastoma inversely correlates with patient survival [85]. In contrast to the previously observed positive relation in breast cancer [43,86], Guo et al observed an inverse correlation between DYRK2 expression and survival in the same cancer subtype [66].…”
Section: Dyrk2 and Diseasementioning
confidence: 99%
“…As a cell permeable inhibitor, it is commonly used to study DYRK family functionality [92]. It inhibits cell proliferation, migration, and invasion in several human cancer cell lines [85,93].…”
Section: Pharmacological Inhibition Of Dyrk2mentioning
confidence: 99%